Adopting a student-led pedagogic approach within higher education: the reflections of an early career academic. Issue 1 (2nd January 2018) - Rowley, Chris; Fook, Janis; Glazzard, Jonathan
Abstract: The current paper presents a reflective account of the adoption of a student-led pedagogic approach, based upon the first author's experiences of working within a new academic institution. Carl Rogers' writings around student-centred learning and the role of the facilitator provide the theoretical underpinning for the reflections put forward, and contextual information regarding the institution's learning and teaching strategy, and the first author's teaching background are also provided. Observations and reflections relating to 'power' within teaching and learning, and the challenges (and successes) encountered when adopting the role of a 'facilitator of learning' are considered from a critical standpoint. The paper closes with some key questions and considerations surrounding the first author's ongoing exploration of this innovative pedagogic approach.